The name of God is mercy : a conversation with Andrea Tornielli - Francis, Pope, 1936-; Tornielli, Andrea, 1964-; Stransky, Oonagh (New York : Random House Large Print, 2016)
"In his first official book published as Pope, in celebration of his Jubilee of Mercy, Pope Francis here addresses all humanity in an intimate and personal dialogue. At the center of this book is the subject closest to his heart--mercy--which has long been the cornerstone of his faith and is now the central teaching of his papacy. These pages resonate with a desire to reach all those souls who are looking for meaning in life, a road to peace and reconciliation, and the healing of physical and spiritual wounds"--Amazon.com.
A Time for Mercy -- The Gift of Confession -- Looking for the Smallest Opening -- A Sinner, Like Simon Peter -- Too Much Mercy? -- Shepherds, Not Scholars of the Law -- Sinners Yes, Corrupt No -- Mercy and Compassion -- Living the Holy Year of Mercy.
Includes bibliographical references (pages 217-218).
Keywords: Catholic Church -- Doctrines; Mercy; Large type books